2020
DOI: 10.3758/s13423-020-01780-1
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual variability: Implications for learning and generalization

Abstract: The generalization of learned behavior has been extensively investigated, but accounting for variance in generalized responding remains a challenge. Based on recent advances, we demonstrate that the inclusion of perceptual measures in generalization research may lead to a better understanding of both intra-and interindividual differences in generalization. We explore various ways through which perceptual variability can influence generalized responding. We investigate its impact on the ability to discriminate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 136 publications
2
25
0
Order By: Relevance
“…Therefore, poor performance on the current task may actually reflect poor CS memory. In a recent study, we demonstrated that increased perceptual memory uncertainty about the CS was associated with broader generalization gradients, much like those we found for the bad perceivers (Zenses et al, 2020). Other studies have demonstrated that associative learning is capable of altering the ability to discriminate between stimuli (Laufer & Paz, 2012;Resnik, Sobel, & Paz, 2011;Schechtman, Laufer, & Paz, 2010) with inter-individual differences in the extent of learning-induced changes (Laufer, Israeli, & Paz, 2016).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Therefore, poor performance on the current task may actually reflect poor CS memory. In a recent study, we demonstrated that increased perceptual memory uncertainty about the CS was associated with broader generalization gradients, much like those we found for the bad perceivers (Zenses et al, 2020). Other studies have demonstrated that associative learning is capable of altering the ability to discriminate between stimuli (Laufer & Paz, 2012;Resnik, Sobel, & Paz, 2011;Schechtman, Laufer, & Paz, 2010) with inter-individual differences in the extent of learning-induced changes (Laufer, Israeli, & Paz, 2016).…”
Section: Discussionsupporting
confidence: 81%
“…How we respond to novel stimuli is the outcome of a process that is luckily not based solely on randomness but relies on different sources of information to generate an adaptive response (Zaman, Chalkia, et al, 2020). This ability to generalize from previous learning is highly functional as it makes optimal use of acquired knowledge in order to avoid unnecessary (re)learning and costly mistakes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, it is notable that the problem of specifying input representations for models of neural/cognitive function appears to apply more generally to many different fields of research. For instance, recent work in category learning (Roark et al, 2020), perceptual learning (Zaman et al, 2020) and visual memory (Schurgin et al, 2020) supports a more general case that many well-established theories about underlying processes have made assumptions about the representation of physical stimulus properties as inputs that on examination are problematic. Firstly, it has been noted that assumptions made in one stimulus domain (e.g.…”
Section: Representation Algorithm and Abstract Modelmentioning
confidence: 99%